MODERN APPROACHES TO ENSURING THE SAFETY OF MEDICAL PERSONNEL WHEN WORKING WITH CARCINOGENIC SUBSTANCES, INCLUDING CYTOSTATICS - Alenitskaya, Marina Vladimirovna; Tokareva, Elvira Olegovna (Medicine in Kuzbass, 2026)
Antitumor drugs pose a significant occupational risk to medical personnel due to their cytotoxic, mutagenic, carcinogenic and teratogenic properties.Objective – to identify modern approaches to the protection of medical personnel from the harmful effects of carcinogenic substances during preparation and administration in the world, to identify strategic approaches to create safety in the future.Materials and methods. An analysis of international regulatory documents, scientific publications and Russian regulations in the field of occupational safety when working with cytostatics has been carried out.Results. It has been established that medical personnel working with antitumor drugs are at risk of developing long-term consequences, including oncological diseases, reproductive disorders and genetic damage. Studies confirm the presence of trace amounts of cytostatics in the biological environments of personnel, even if standard precautions are followed. International experience demonstrates the effectiveness of an integrated approach, including the use of Class II laminar flow cabinets or pharmaceutical insulators.; use of closed drug transfer systems (CSTD); mandatory use of personal protective equipment; development of standard operating procedures; regular monitoring of staff health status.In the Russian Federation, the working conditions of personnel working with cytostatics are classified as class 3.4 of harmfulness, however, the regulatory framework requires improvement in terms of detailing requirements for equipment and procedures.Conclusion. To ensure the safety of medical personnel, it is necessary to develop and implement a national concept, including the modernization of the regulatory framework, the introduction of modern protection technologies and the creation of an occupational risk monitoring system.
Keywords: antitumor drugs; occupational safety; medical personnel; cytostatic drugs; carcinogens; closed systems